Repeated resection-associated breast angiosarcoma: A case report. Issue 39 (September 2018) - Tang, Tiantian; Li, Haiping
Abstract: Rationale: As a very rare vascular tumor, breast angiosarcoma (AS) can be divided into primary and second breast AS. However, the latter is slightly more commonly detected in clinical practice. Radiation post mastectomy is the common cause for the secondary breast AS, and although there are other reasons, it is still quite rare. In the present study, we reported a rare case of breast AS and summarized the relevant literatures so that to conduce to diagnose AS. Patient concerns: A 50-year-old female with a history of right breast neoplasm was treated with repeat lumpectomy for 4 times during 8 years. Diagnoses: Mammogram and ultrasound examination demonstrated a possible malignancy (BIRADS-4B and BI-RADS-4C, respectively). Immunohistochemically positive for endothelial markers CD31, CD34, ERG, and FVIII-R-Ag. Interventions: The patient underwent a right mastectomy with sentinel lymph node biopsy by our multidisciplinary team and no other therapy was given postsurgery. Outcomes: The patient had no recurrence after 3 months. Lessons: Based on our findings, we concluded that repeated resection might be a risk factor for the breast AS, especially for a gradual pathological evolution from benign to malignant. This case showed a very rare cause for angiomatosis of breast, and the patient had a successful outcome after a simple mastectomy.